Mindfulness-based Practices in Workers to Address Mental Health Conditions: A Systematic Review - Quentin Durand-Moreau; Tanya Jackson; Danika Deibert; Charl Els; Janice Y. Kung; Sebastian Straube (Safety and Health at Work, 2023)
The effectiveness of mindfulness techniques in addressing mental health conditions in workers is uncertain. However, it could represent a therapeutic tool for workers presenting with such conditions. Our objective was to assess the effects of mindfulness-based practices for workers diagnosed with mental health conditions. We conducted a systematic review of randomized controlled trials. Participants included were workers with a mental health condition. Interventions included any mindfulness technique, compared to any nonmindfulness interventions. Outcomes were scores on validated psychiatric rating scales. A total of 4,407 records were screened; 202 were included for full-text analysis; 2 studies were included. The first study (Finnes et al., 2017) used Acceptance and Commitment Therapy (ACT) associated or not with Workplace Dialogue Intervention (WDI), compared to treatment as usual. At 9 months follow-up, for the ACT group, depression scores improved marginally (standardized mean difference [SMD]: -0.06, p = 0.021), but anxiety scores were worse (SMD: 0.15, p = 0.036). Changes in mental health outcomes were not statistically significant for the ACT + WDI group. In the second study (Grensman et al., 2018), no statistically significant change in mental health scales has been observed after completion of mindfulness-based cognitive therapy compared to cognitive behavioral therapy. Substantial heterogeneity precluded meta-analysis. This systematic review did not find evidence that mindfulness-based practices provide a durable and substantial improvement of mental health outcomes in workers diagnosed with mental health conditions.